Control of Banana Wilt Disease Caused by Fusarium oxysporum Schlecht f.sp. cubense (E. F. Smith) Using Crab Shell Powder and Chitosan - Widodo Widodo; Heri Harti; Suryo Wiyono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
This research was conducted to evaluate the effectiveness of crab shell powder and chitosan to control Fusarium wilt disease on bananas and to analyze the involved control mechanisms. The effectiveness of crab shell powder and chitosan to F. oxysporum f.sp. cubense was examined in a laboratory (in vitro) and greenhouse (in planta). In vitro evaluation showed that chitosan has an antifungal effect while crab shell powder did not. Application of crab shell powder and chitosan suppressed the disease in green house test. The concentrations of crab shell powder and chitosan that most effective to control Fusarium wilt incidences were 0.25% and 0.10% with an efficacy rate of 66.7% and 83.3%, respectively. The highest disease severity reduction was showed by crab shell powder 0.25% and chitosan 0.50% with an efficacy rate of 56.8% and 59.4%, respectively. Suppression of the disease might be due to the fungicidal effect of chitosan and the increase of the total population of bacteria and chitinolytic bacteria in the rhizosphere when banana seedling roots were treated with crab shell powder or chitosan. Experiment results using the split roots technique exhibited the role of crab shell powder and chitosan potentially to induce the resistance of banana to Fusarium wilt.